Identifikasi Somaklon Padi Gajahmungkur, Towuti dan IR 64 Tahan Kekeringan Menggunakan Polyethylene Glycol - Endang Gati Lestari; Ika Mariska (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2006)
The drought stress tolerant and high yielding rice is needed in upland rice system. The changing global climate makes dry season longer, resulting in the reduction of rice production. There should be an effort to introduce new variety of high-yielding and drought tolerant rice. In this attempt, research was conducted to improve the genetic of Indica rice, particularly Gajahmungkur, Towuti and IR 64 varieties in order to find the somaclones with the characteristics above. As an approach, gamma-ray mutative induction was applied to be followed by selection in PEG. The regenerated shoot from the irradiated callus was then selected and acclimatisized in the greenhouse to obtain eighty three somaclones from the three varieties. PEG (molecular weight 6000) was applied to obtain the drought-tolerant somaclone. PEG was a selective agent used by which populations could be selected in a short time. Treatment with 20% PEG (equals to osmotic potential 1.2 Mpa) on the rice produced 16 somaclones from Gajahmungkur, 12 from Towuti and 18 from IR 64 putatively drought tolerant. Key words : Oryza sativa, drought tolerance, PEG